The Immune Landscape of Prostate Cancer and Nomination of PD-L2 as a Potential Therapeutic Target. (13th October 2018) - Zhao, Shuang G; Lehrer, Jonathan; Chang, S Laura; Das, Rajdeep; Erho, Nicholas; Liu, Yang; Sjöström, Martin; Den, Robert B; Freedland, Stephen J; Klein, Eric A; Karnes, R Jeffrey; Schaeffer, Edward M; et al.
Abstract: Background: Immunotherapy has been less successful in treating prostate cancer than other solid tumors. We sought to better understand the immune landscape in prostate cancer and identify immune-related biomarkers and potential therapeutic targets. Methods: We analyzed gene expression data from 7826 prospectively collected prostatectomy samples (2013–2016), and 1567 retrospective samples with long-term clinical outcomes, for a total of 9393 samples, all profiled on the same commercial clinical platform in a CLIA-certified lab. The primary outcome was distant metastasis-free survival (DMFS). Secondary outcomes included biochemical recurrence-free survival (bRFS), prostate cancer-specific survival (PCSS), and overall survival (OS). All statistical tests were two-sided. Results: Unsupervised hierarchical clustering of hallmark pathways demonstrated an immune-related tumor cluster. Increased estimated immune content scores based on immune-specific genes from the literature were associated with worse bRFS (hazard ratio [HR] = 1.26 [95% confidence interval [CI] = 1.12 to 1.42]; P  < .001), DMFS (HR = 1.34 [95% CI = 1.13 to 1.58]; P  < .001), PCSS (HR = 1.53 [95% CI = 1.21 to 1.92]; P  < .001), and OS (HR = 1.27 [95% CI = 1.07 to 1.50]; P  = .006). Deconvolution using Cibersort revealed that mast cells, natural killer cells, and dendritic cells conferred improved DMFS, whereas macrophages and T-cells conferred worse DMFS. Interestingly, while PD-L1 was not prognostic, consistent with its low expression in prostate cancer, PD-L2 was expressed at statistically significantly higher levels ( P  < .001) and was associated with worse bRFS (HR = 1.17 [95% CI = 1.03 to 1.33]; P  = .01), DMFS (HR = 1.25 [95% CI = 1.05 to 1.49]; P  = .01), and PCSS (HR = 1.45 [95% CI = 1.13 to 1.86]; P  = .003). PD-L2 was strongly associated with immune-related pathways on gene set enrichment analysis suggesting that it is playing an important role in immune modulation in clinical prostate cancer samples. Furthermore, PD-L2 was correlated with radiation response pathways, and also predicted response to postoperative radiation therapy (PORT) on multivariable interaction analysis ( P  = .03). Conclusion: In the largest study of its kind to date, these results illustrate the complex relationship between the tumor-immune interaction, prognosis, and response to radiotherapy, and nominate PD-L2 as a potential novel therapeutic target in prostate cancer, potentially in combination with radiotherapy.